Neurogenesis and Inflammation after Ischemic Stroke: What is Known and Where We Go from Here. Issue 10 (October 2014) - Tobin, Matthew K; Bonds, Jacqueline A; Minshall, Richard D; Pelligrino, Dale A; Testai, Fernando D; Lazarov, Orly
This review covers the pathogenesis of ischemic stroke and future directions regarding therapeutic options after injury. Ischemic stroke is a devastating disease process affecting millions of people worldwide every year. The mechanisms underlying the pathophysiology of stroke are not fully understood but there is increasing evidence demonstrating the contribution of inflammation to the drastic changes after cerebral ischemia. This inflammation not only immediately affects the infarcted tissue but also causes long-term damage in the ischemic penumbra. Furthermore, the interaction between inflammation and subsequent neurogenesis is not well understood but the close relationship between these two processes has garnered significant interest in the last decade or so. Current approved therapy for stroke involving pharmacological thrombolysis is limited in its efficacy and new treatment strategies need to be investigated. Research aimed at new therapies is largely about transplantation of neural stem cells and using endogenous progenitor cells to promote brain repair. By understanding the interaction between inflammation and neurogenesis, new potential therapies could be developed to further establish brain repair mechanisms.